2013
DOI: 10.1103/physrevlett.111.057204
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Thermal Relaxation in Artificial Spin Ice

Abstract: We study the thermal relaxation of artificial spin ice with photoemission electron microscopy, and are able to directly observe how such a system finds its way from an energetically excited state to the ground state. On plotting vertex-type populations as a function of time, we can characterize the relaxation, which occurs in two stages, namely a string and a domain regime. Kinetic Monte Carlo simulations agree well with the temporal evolution of the magnetic state when including disorder, and the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
239
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(255 citation statements)
references
References 30 publications
15
239
1
Order By: Relevance
“…Because the rate at which thermal fluctuations occur depends very sensitively on island thickness, this ensured that some of the arrays would undergo observable thermal fluctuations near room temperature. We found that 3 to 3.5 nm thick arrays were thermally active around room temperature, consistent with previous studies 17,18 . A 2 nm capping layer of Al was deposited on top of the permalloy to inhibit oxidation.…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…Because the rate at which thermal fluctuations occur depends very sensitively on island thickness, this ensured that some of the arrays would undergo observable thermal fluctuations near room temperature. We found that 3 to 3.5 nm thick arrays were thermally active around room temperature, consistent with previous studies 17,18 . A 2 nm capping layer of Al was deposited on top of the permalloy to inhibit oxidation.…”
Section: Methodssupporting
confidence: 81%
“…A 2 nm capping layer of Al was deposited on top of the permalloy to inhibit oxidation. The island dimensions (470×170×3 nm) were similar to those used in previous studies 17,18 of thermally active artificial spin ice, which facilitates comparison. Also, because these islands are thermally active around room temperature, problems associated with thicker islands (high temperature annealing and associated complications involving substrate-island interdiffusion 10 ) are avoided.…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…Despite theoretical predictions [47], however, a complete GS has not been achieved in nanomagnetic ice systems; instead, only short-range-ordered GS can be reached experimentally by rotating-field demagnetization protocols [43,70]. Only recently, the long-rangeordered ground state has been achieved nearly perfectly over extended regions using a single-shot thermal annealing technique during fabrication [51,94] and a thermally induced melting-freezing protocol is presented to explore experimentally the formation of thermally induced long-range ground-state ordering in a square artificial spin-ice systems of elongated ferromagnetic nanoislands [95][96][97]. A long-range ground-state magnetic ordering region separated by chains of higher energy vertex configurations has been observed.…”
Section: Ice Ground State Of Square Skyrmion Icementioning
confidence: 99%